Foraminifera-bound nitrogen isotope data from Site 999 - Farmer, Jesse R; Martínez-García, Alfredo; Sentman, Lori; Schiebel, Ralf; Arns, Anthea; Yehudai, Maayan; Tiedemann, Ralf; Sigman, Daniel M; Haug, Gerald H (In: Farmer, JR et al. (2025): Early Pliocene foraminifera-bound nitrogen isotopes and oxygen isotopic composition of seawater from ODP Sites 999 and 1241 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974971, 2025)
Early Pliocene foraminifera-bound nitrogen isotope data from ODP Site 165-999A in Trilobatus sacculifer and full procedural replicate precision (when measured).
Keywords: Foraminifera-bound nitrogen isotopes; Mg/Ca-based sea surface temperature; oxygen isotope ratios; Seawater δ18O